Contoured Loop and Modified Wiring Technique for occipitocervical Fixation - A Safe and Efficacious Option - Shrestha, Shikher; Bishokarma, Suresh; Devkota, Upendra Prasad (Nepal Journal of Neuroscience, 2018)
To study the safety and efficacy of contoured loop and modified wiring techniques for occipitocervical fixation. Retrospective study among 15 patients who underwent occipitocervical fixation from Jan 2011-16 were reviewed. Contoured loop was wired at 2 points in occiput and 4 different points, 2 on either side to percutaneously passed K wire through the spino laminar junctions of C2 and C3. Additional fusion with on lay autologous graft from either iliac crest or ribs was done. Various parameters studied were patient’s demography, causes of instability, change in neurological function, complications and radiographic outcome. Six had basilar in vagination, 4 had traumatic atlantoaxial subluxation, 4 had osodontoidium and 1 had Rheumatoid arthropathy. There was improvement in Frankel grade from C to D in 6 and from D to E in 5 patients. Radiological union at 6 months was observed in all 15 cases. Two patients had surgical site infection. Dislodgement of K wire was found in 4 cases (26.66%) by which time radiological union had already taken place. The approximate cost of instrumentation was 100 dollars for each patient. Conclusions. Contoured rod and modified wiring occipitocervical fixation technique are relatively a safe, cheap and technically easy alternative for the management of occipitocervical instability.